Preface to the presidency : selected speeches of Bill Clinton, 1974-1992 - Clinton, Bill, 1946- (University of Arkansas Press, 1996)
Bill Clinton has long been touted as a master of public speaking form and political discourse. Taken from his speeches as a twenty-seven-year-old candidate for Congress though his 1992 victory speech, Preface to the Presidency reveals the power and range of his contribution to our nation's political dialogue.